Optic Disc Swelling and Vision Loss in a Patient with Cystic Fibrosis and Diabetes - Ioulia Iosfina; Jean Y. Chuo; Derek V. Godinho; Pearce G. Wilcox; Stuart H. Kreisman; Bradley S. Quon (Case Reports in Endocrinology)
Advances in cystic fibrosis management have significantly improved life expectancy in these patients. However, we are now faced with a growing number of long-term extrapulmonary consequences of this disease, including ophthalmic complications of diabetes in cystic fibrosis patients. We present a unique report that documents a case of diabetic papillopathy progressing to nonarteritic anterior ischemic optic neuropathy resulting in vision loss in a patient with CF and diabetes. It highlights the potentially devastating consequences of longstanding diabetes in CF patients.